Linguistic interpretation of the whole concept, which represents the image of "PARENTS" in the of young people. - Abdimurodov Doston Dilmurod ugli; Usmonova Yulduz Bozor qizi (Zien Journals, 2022)
This article seeks to reveal the attitudes, perceptions, and duties of parents to their parents through linguistic means in the minds of the younger generation
Keywords: Parent; father; mother; duty